STRATEGIES FOR DEVELOPING MARINE ECOTOURISM BASED ON TURTLE CONSERVATION IN PEKIK NYARING VILLAGE, CENTRAL BENGKULU REGENCY - Jaya, Sutrisman Amei; Mudzakir, Abdul Kohar; Wardini, Tuty Maria (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2024)
The conservation of turtles in Pekik Nyaring Village presents a unique opportunity to develop marine ecotourism, significantly enhancing local socio-economic conditions. This research aims to evaluate socio-economic aspects, assess community participation and roles, and identify strategies to advance turtle conservation-based ecotourism in the village. Using descriptive, qualitative, and quantitative methods, including questionnaires, the study focuses on the 4,162 residents of Pekik Nyaring Village, with a sample of 30 respondents. Primary and secondary data sources will be utilized, and a SWOT analysis will be conducted. The SWOT analysis indicates that the development of turtle conservation ecotourism in Pekik Nyaring falls into the WO (Weaknesses-Opportunities) quadrant. Recommended actions include establishing effective coordination between turtle conservation managers and the local government, strengthening community institutions involved in conservation efforts, and leveraging mass media to promote turtle conservation ecotourism through social media and dedicated websites. These strategies aim to inform tourists about ongoing developments and enhance the visibility of turtle conservation efforts in Pekik Nyaring Village.